1998
DOI: 10.1038/sj.ejcn.1600572
|View full text |Cite
|
Sign up to set email alerts
|

Delayed gastric emptying rate may explain improved glycaemia in healthy subjects to a starchy meal with added vinegar

Abstract: Objectives: The aim of the study was to evaluate the possible in¯uence of acetic acid (administered as vinegar) on the postprandial glucose and insulin responses, and the potential involvement of a modi®ed gastric emptying rate was studied by use of paracetamol as a marker. Design: The white bread reference meal as well as the corresponding meal supplemented with vinegar had the same content of starch, protein and fat. The meals were served in the morning after an over-night fast and in random order. Capillary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
160
1
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 234 publications
(173 citation statements)
references
References 11 publications
9
160
1
3
Order By: Relevance
“…However, the lowered available starch content per se does not explain the lowered GI (Jenkins et al, 1987;Wolever, 1990;Raben et al, 1994;Björck et al, 2000). The mechanism by which organic acids reduce glycaemia and insulinaemia to, for example, white bread and rice (Liljeberg & Björck, 1998;Sugiyama et al, 2003) is not fully understood. In the case of acetic acid, the magnitude of reduction in glycaemia may be as much as 35%, depending on the level of acetic acid.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the lowered available starch content per se does not explain the lowered GI (Jenkins et al, 1987;Wolever, 1990;Raben et al, 1994;Björck et al, 2000). The mechanism by which organic acids reduce glycaemia and insulinaemia to, for example, white bread and rice (Liljeberg & Björck, 1998;Sugiyama et al, 2003) is not fully understood. In the case of acetic acid, the magnitude of reduction in glycaemia may be as much as 35%, depending on the level of acetic acid.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of acetic acid, the magnitude of reduction in glycaemia may be as much as 35%, depending on the level of acetic acid. Brighenti et al (1995) suggested that the acetic acid caused an inhibition of the amylases whereas others have found evidence of a delay in gastric emptying rate (Liljeberg & Björck, 1998). The studies mentioned above have been performed in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations